2022
DOI: 10.3390/brainsci12070887
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Oxygenation-Guided Therapy and Outcome in Traumatic Brain Injury: A Single-Center Matched Cohort Study

Abstract: Brain tissue oxygenation (PbtO2)-guided therapy can improve the neurological outcome of traumatic brain injury (TBI) patients. With several Phase-III ongoing studies, most of the existing evidence is based on before-after cohort studies and a phase-II randomized trial. The aim of this study was to assess the effectiveness of PbtO2-guided therapy in a single-center cohort. We performed a retrospective analysis of consecutive severe TBI patients admitted to our center who received either intracranial pressure (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, our meta-analysis results revealed that PbtO 2 monitoring was associated with extended hospital length of stay. Although the severity of TBI at admission was comparable between patient groups, the difference may be attributed to patients in the PtbO 2 monitoring group receiving more intensive life-support treatments, potentially leading to prolonged survival [ 18 ]. The relationship between PbtO 2 monitoring and extended hospital length of stay in patients with TBI, therefore, needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our meta-analysis results revealed that PbtO 2 monitoring was associated with extended hospital length of stay. Although the severity of TBI at admission was comparable between patient groups, the difference may be attributed to patients in the PtbO 2 monitoring group receiving more intensive life-support treatments, potentially leading to prolonged survival [ 18 ]. The relationship between PbtO 2 monitoring and extended hospital length of stay in patients with TBI, therefore, needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…not reporting outcomes of interest (163 articles), case report (46 articles), or meta-analysis or systematic review (43 articles). Eleven articles that met all conditions were identified using full-text screening and included in the final analysis [13,[16][17][18][19][20][21][22][23][24][25].…”
Section: Quality Evaluationmentioning
confidence: 99%
“…When multiple publications of the same research group or center described case series with potential overlap, the more recent publication, if eligible, was considered. We also included into the systematic review a recent study from our group, which was concomitantly submitted with the present work and subsequently published [23].…”
Section: Data Sources and Study Selectionmentioning
confidence: 99%
“…The studies targeted an ICP < 20 mm Hg, a PbtO 2 > 10-25 mm Hg, and a CPP > 50-70 mm Hg; the most frequently used thresholds for PbtO 2 and CPP were > 20 mm Hg and > 60 mm Hg, respectively (Table 1) [15, 17-19, 21, 29-33]. The duration of intracranial hypertension and tissue hypoxia that triggered an intervention was reported in five studies: three studies used an ICP threshold of > 20 mm Hg for more than 5 min [16,20,34], whereas one study used an ICP > 20 mm Hg for 2 min [18]. Regarding tissue hypoxia, two studies used a PbtO 2 < 20 mm Hg for 5 min [16,34], whereas one used a PbtO 2 < 15 mm Hg for 5 min [30].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation